Geochemistry of water and sediment from selected river in Kundang- Ranau, Sabah - A.N.A. Malik; S.A. Rahim; Hennie Fitria Wulandary Soehady Erfen; Baba Musta (Faculty of Science and Natural Resources, 2020)
The study area located in Kundasang and Ranau, Sabah. The area is underlain by the Trusmadi Formation, ultrabasic rock, and Gravel Pinousuk. In this study, a river and streams around Kundasang and Ranau have been chosen for geochemical analysis of sediments and water. Physico-chemical analysis of water shows the pH water ranged from slightly acidic (6.47) to slightly neutral which is 7.14, while pH of each sediments from each stream recorded are slightly acidic with the range from 5.54 to 6.96. The result of TSS analysis shows the value between 20.24 mgTSS/L to 3170.73 mgTSS/L. An electric conductivity (µS/cm) of each stream ranged in the index of 0 based on the index table of electric conductivity. The Fe has the highest concentration with the average of 30.14mg/L, followed by Mn with 8.99mg/L and Zn with 2.88mg/L. The average concentration of Cu is 2.72mg/L, whereas Cr and Pb was less than 1.0 mg/L.